2015
DOI: 10.1007/s11999-015-4321-y
|View full text |Cite
|
Sign up to set email alerts
|

Acetate Templating on Digital Images Is More Accurate Than Computer-based Templating for Total Hip Arthroplasty

Abstract: Background Templating is an important aspect of preoperative planning for total hip arthroplasty and can help determine the size and positioning of the prosthesis. Historically, templating has been performed using acetate templates over printed radiographs. As a result of the increasing use of digital imaging, surgeons now either obtain additional printed radiographs solely for templating purposes or use specialized digital templating software, both of which carry additional cost. Questions/purposes The purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
72
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(86 citation statements)
references
References 26 publications
5
72
0
9
Order By: Relevance
“…An increasing number of studies aim to evaluate the accuracy, precision and reliability of preoperative templating in THA, and the results are predominantly reported in favour of templating (10)(11)(12)(13)(14)(15). Most publications follow the example of Knight and Atwater, who used a ±1 size approximation of the component sizes in their evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of studies aim to evaluate the accuracy, precision and reliability of preoperative templating in THA, and the results are predominantly reported in favour of templating (10)(11)(12)(13)(14)(15). Most publications follow the example of Knight and Atwater, who used a ±1 size approximation of the component sizes in their evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The results are predominantly reported as favourable, and the recommendation to utilize the method is strong (15). However, most studies report on at least partially cemented prostheses, which is less dictated by anatomical constraints than uncemented prostheses.…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative on-screen templating methods have been described in several earlier papers1314151617). Petretta et al17) compared acetate templating of digitally calibrated images on an liquid crystal display (LCD) monitor to digital templating in their 52 THAs, and concluded that acetate onlay templating on digitally calibrated images can be a reliable substitute for digital templating.…”
Section: Discussionmentioning
confidence: 99%
“…Petretta et al17) compared acetate templating of digitally calibrated images on an liquid crystal display (LCD) monitor to digital templating in their 52 THAs, and concluded that acetate onlay templating on digitally calibrated images can be a reliable substitute for digital templating. Krishnamoorthy et al13) also studied the accuracy and reliability of templating the acetabular cup size using conventional acetate templates on digital radiographs, and they reported 90% prediction rate for the acetabular cup size within ±1 size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation